FEATURES OF CONROL OF LABOUR COMPENSATION - A. Volkova; T. Rogulenko (Вестник университета, 2017)
The author analyzed the features of the control of remuneration in the formation of accounting information on payroll industry poultry. The improvement of information and methodical support of accounting systems and internal control involves the modification of organizational structure of service of internal control, clarifying its functions and objectives. In the framework of this article. This article illustrates the organizational and functional structure of the internal control service, designed for businesses of poultry, which can be used by other economic actors in the sphere of poultry farming.